LetsTalkShots: personalized vaccine risk communication - Salmon, Daniel A.; Dudley, Matthew Z.; Brewer, Janesse; Shaw, Jana; Schuh, Holly B.; Proveaux, Tina M.; Jamison, Amelia M.; Forr, Amanda; Goryn, Michelle; Breiman, Robert F.; Orenstein, Walter A.; Kao, Lee-Sien; et al. (Frontiers in Public Health, 2023)
Introduction Vaccine hesitancy is a global health threat undermining control of many vaccine-preventable diseases. Patient-level education has largely been ineffective in reducing vaccine concerns and increasing vaccine uptake. We built and evaluated a personalized vaccine risk communication website called LetsTalkShots in English, Spanish and French (Canadian) for vaccines across the lifespan. LetsTalkShots tailors lived experiences, credible sources and informational animations to disseminate the right message from the right messenger to the right person, applying a broad range of behavioral theories. Methods We used mixed-methods research to test our animation and some aspects of credible sources and personal narratives. We conducted 67 discussion groups (n = 325 persons), stratified by race/ethnicity (African American, Hispanic, and White people) and population (e.g., parents, pregnant women, adolescents, younger adults, and older adults). Using a large Ipsos survey among English-speaking respondents (n = 2,272), we tested animations aligned with vaccine concerns and specific to population (e.g., parents of children, parents of adolescents, younger adults, older adults). Results Discussion groups provided robust feedback specific to each animation as well as areas for improvements across animations. Most respondents indicated that the information presented was interesting (85.5%), clear (96.0%), helpful (87.0%), and trustworthy (82.2%). Discussion Tailored vaccine risk communication can assist decision makers as they consider vaccination for themselves, their families, and their communities. LetsTalkShots presents a model for personalized communication in other areas of medicine and public health.